2008
DOI: 10.1080/03630260802004269
|View full text |Cite
|
Sign up to set email alerts
|

Results of the National Program for Prevention of β-Thalassemia Major in the Iranian Province of Mazandaran

Abstract: Prevention programs are considered to be a top priority in Iran because beta-thalassemia (beta-thal) major (TM) is the most common autosomal disorder in Iran, and in the Mazandaran Province in particular. The main strategies comprise providing appropriate information for the public and professionals, screening and counseling of families at-risk and screening of general population prior to marriage. Providing laboratories for prenatal diagnosis was the most recent step in the program. We report the results of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 8 publications
0
51
0
Order By: Relevance
“…The first study conducted by Samavat et al (14) in 2004, and another one in 2007 (15) showed a significant success in decreasing the rate of thalassemia newborns, which was further validated by other studies (16)(17)(18). Khorasani et al (16) in a study to evaluate the success of the program concluded that the TPP has significantly reduced the financial burden upon thalassemic patients and their families.…”
Section: Discussionmentioning
confidence: 84%
“…The first study conducted by Samavat et al (14) in 2004, and another one in 2007 (15) showed a significant success in decreasing the rate of thalassemia newborns, which was further validated by other studies (16)(17)(18). Khorasani et al (16) in a study to evaluate the success of the program concluded that the TPP has significantly reduced the financial burden upon thalassemic patients and their families.…”
Section: Discussionmentioning
confidence: 84%
“…Carrier detection and genetic counseling programs have been very successful in reducing the birth prevalence of inherited disorders in some populations, such as in Iran (Khorasani et al 2008;Samavat and Modell 2004). These programs are most successful when they are sensitive to the cultural backgrounds of populations in which they are applied.…”
Section: Preconception and Premarital Counseling For Consanguinitymentioning
confidence: 99%
“…3 Nevertheless, some countries including Iran, Saudi Arabia, Palestinian Territories and Cyprus have laws in place making premarital screening for haemoglobinopathies mandatory for all couples before they are given approval to get married. 9,[20][21][22][23][24][25][26] This raises ethical questions, as couples are unable to voluntarily decide for themselves whether they would like to undergo genetic screening. Thalassaemia carrier screening has been included as part of an existing mandatory premarital blood test in Iran since 1991.…”
Section: Mandatory Screeningmentioning
confidence: 99%
“…Thalassaemia carrier screening has been included as part of an existing mandatory premarital blood test in Iran since 1991. [22][23][24] This form of mandatory premarital thalassaemia screening also began in the Gaza Strip in 2000 9 and in Saudi Arabia in 2003. 20 Carrier couples receive advice on the options available to them, one of which is cancellation of marriage, and they can then decide whether to marry each other.…”
Section: Mandatory Screeningmentioning
confidence: 99%